Development of Automatic Welding System for Offshore Platform Pile Pipe - XU Jia-zhong; ZHANG Yu; YOU Bo; LI Dong-jie; FU Wei (Journal of Harbin University of Science and Technology)
Twin arc welding system for offshore platform pile pipe with multipoint dual power and a single molten pool is put forward in this paper in order to solve the problems of low producing efficiency and operating inconvenience in complex environment. Welding tractor，double welding gun adjusting mechanism and 120 degrees circumferential butt joint guide rail are designed. Monofilament AC manual gas protection welding machine internal timing and motion motor are under real-time control Based on PLC. We elaborate the control requirement of the system，hardware configuration，software design and human-machine interface design，and complete the pile pipe girth welding test and technological parameter selection. The experimental results show that the system is stable and reliable，and the butt weld of the pile pipe is good，and the quality of the radiographic inspection is qualified， which fully meets the requirements of the construction of the pile pipe in the docking site of the offshore platform.